2013
DOI: 10.1371/journal.pone.0083561
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Dendritic Spine Density and Morphology in the Superficial Layers of the Medial Entorhinal Cortex Induced by Extremely Low-Frequency Magnetic Field Exposure

Abstract: In the present study, we investigated the effects of chronic exposure (14 and 28 days) to a 0.5 mT 50 Hz extremely low-frequency magnetic field (ELM) on the dendritic spine density and shape in the superficial layers of the medial entorhinal cortex (MEC). We performed Golgi staining to reveal the dendritic spines of the principal neurons in rats. The results showed that ELM exposure induced a decrease in the spine density in the dendrites of stellate neurons and the basal dendrites of pyramidal neurons at both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…One possible biological substrate for this effect is the modulation of "synaptic plasticity," which is one plausible candidate for explaining the persistence of effects after exposure, and also that effects take place after some time [Modolo et al, 2013a,b]. This possibility is supported by recent experimental results on synaptic plasticity mechanisms in rats exposed to 50 Hz MF [Xiong et al, 2013]. To summarize, our results do not provide support for acute effects on brain electrical activity and functional activation due to 60 Hz sinusoidal MF exposure up to 7.6 mT (i.e., about 76,000 times higher than typical daily exposure of public to power-line frequency MF).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…One possible biological substrate for this effect is the modulation of "synaptic plasticity," which is one plausible candidate for explaining the persistence of effects after exposure, and also that effects take place after some time [Modolo et al, 2013a,b]. This possibility is supported by recent experimental results on synaptic plasticity mechanisms in rats exposed to 50 Hz MF [Xiong et al, 2013]. To summarize, our results do not provide support for acute effects on brain electrical activity and functional activation due to 60 Hz sinusoidal MF exposure up to 7.6 mT (i.e., about 76,000 times higher than typical daily exposure of public to power-line frequency MF).…”
Section: Discussionmentioning
confidence: 91%
“…Reported effects of ELF MF on brain activity often indicate that human EEG is prone to modulation in the occipital lobe in the alpha band [Cook et al, , ; Ghione et al, ]. Importantly, the duration of exposure is a critical factor to take into account to address the problem of biological mechanisms involved in the experimentally recorded effect: in the case of biological effects reported after the cessation of prolonged exposure (>30 min), it has been suggested that changes in synaptic plasticity could be involved [Modolo et al, ,] with some recent experimental support for this hypothesis [Xiong et al, ]. In the case of acute exposure, changes in synaptic plasticity are unlikely since such effects take time to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Xiong et al . (2013) demonstrated that ELF MFs exposure can decrease dendritic spine densities 5 . We thus used Golgi staining to investigate the effect of ELF MFs exposure on dendritic spine densities in hippocampal CA1 pyramidal cells.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Xiong et al . (2013) indicated that exposing rats to ELF MFs for 14 or 28 days induced a decrease in spine density in the superficial layers of the medial entorhinal cortex 5 . Since the structure and density of dendritic spines are crucial determinants of neuronal input-output transformations and resulting synaptic plasticity, these data imply that ELF MFs exposure might induce impairment in cognitive functions via reduction of spine number.…”
mentioning
confidence: 99%
“…(2014) indicated that long‐term exposure to ELF‐MF significantly increased anxiety without affecting locomotion, and there was a significant elevation of both GABA and glutamate levels in the hippocampus and hypothalamus of mice exposed . Furthermore, ELF‐MF exposure can change dendritic spine density and morphology in the entorhinal cortical neurons, and had caused a long‐lasting increase in the excitatory state of the neurons in the cortex and hippocampus . Although the effect of ELF‐MFs on the activity of neuronal excitability controlling channels including Ca 2+ ‐active potassium channels and Na + channels have previous investigated, very few studies have investigated the effects of ELF‐MF on ligand‐gated channels, particularly γ‐aminobutyric acid (GABA) type A receptors (GABA A Rs).…”
Section: Introductionmentioning
confidence: 99%